Building community through higher music education: a training program for facilitating musical engagement among older adults - Paolantonio, Paolo; Cavalli, Stefano; Biasutti, Michele; Eiholzer, Hubert; Williamon, Aaron (Frontiers in Psychology, 2023)
Preparing music students to design and carry out community-based initiatives can be an effective way to enhance their employability and their wellbeing. With a large body of evidence now pointing to the benefits of musical engagement for older adults, both for individuals and for society as a whole, there is considerable opportunity and value in training aspiring professional musicians to work with and on behalf of those in their third and fourth age. This article describes a seminar designed by a Swiss conservatoire in collaboration with local nursing homes involving residents and music university students in a 10-week group music making programme. On the basis of the positive results emerged in terms of health, wellbeing and career preparation, we aim to provide information relevant for others to replicate this seminar in other higher music education institutions. Moreover, this paper aims to shed light on the complexity of designing music students’ training so that they acquire the competences needed to deliver meaningful, community-based initiatives alongside their other professional training commitments, and to provide directions for future research. The development and implementation of these points could foster the increase and sustainability of innovative programmes beneficial for older adults, musicians and local communities.